Taxes, innovation and productivity - James Cloyne; Joseba Martinez; Haroon Mumtaz; Paolo Surico (Queen Mary University of London, School of Economics and Finance, 2024)
Using a narrative identification of tax changes in the United States over the post-WWII period, we document that a temporary cut in corporate income tax rates leads to a long-lasting increase in innovation and productivity, whereas changes in personal income tax rates only have short-term effects. We show that the results on corporate taxes are consistent with theories of endogenous growth that feature tax amortisation allowances on intellectual property purchases, as in the tax code of most countries in the world. In contrast, personal taxes work primarily through the response of labour supply, which is as transient as the tax change itself.
Keywords: E23; E62; O32; O34; O38; 330; corporate taxes; narrative identification; TFP; R&D; technological adoption